What really counts : the case for a sustainable and equitable economy - Colman, Ronald (Columbia University Press, 2021)
"Politicians and economists fixate on "growing the economy"--Measured by a country's gross domestic product. But this yardstick counts harmful activities such as greenhouse gas emissions, plastic waste, and cigarette sales as gains, and it ignores environmental protection, voluntary community work, and other benefits. What we measure is a choice, and what is and isn't counted determines what sorts of policies are enacted. How can we shift the focus to well-being and quality of life? What Really Counts is an essential, firsthand story of the promise and challenges of accounting for social, economic, and environmental benefits. Ronald Colman recounts two decades of working with three governments to adopt measures capable of quantifying factors that GDP overlooks. Chronicling his path from Nova Scotia to New Zealand to Bhutan, Colman details the challenge of devising meaningful metrics, the effort to see alternatives realized, and the obstacles that stand in the way of implementing new systems. Reflecting on successes and failures, he considers how to shift policy priorities from a narrow economic growth agenda toward a future built on sustainability and equity. Colman has taken the critique of GDP outside the academy and attempted to realize an alternative. The lessons he offers in What Really Counts are vital for anyone interested in how we can measure what matters-and how better measures can help build a better world"--